2022
DOI: 10.1029/2021gl097617
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Name? On the Use and Significance of the Term “Polar Vortex”

Abstract: This commentary appears in the Special Collection focusing on the Arctic stratospheric "polar vortex" in 2019/2020. But how clear are we about what constitutes a "polar vortex"? Confusion persists in the popular press about what a polar vortex is and how polar vortices relate to extreme weather events. This confusion stems in part from imprecise descriptions by the scientific community.In January 2014, a cold air outbreak (CAO) set record-low minimum temperatures throughout the south central and eastern US (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…The term "tropospheric polar vortex" has a much more limited use in the scientific literature than that of "stratospheric polar vortex." However, following the extreme cold air outbreak over the United States in 2014, polar vortices have received a lot of attention in the mainstream media and popular science websites, which has resulted in increased usage in the scientific literature (see Manney et al 2022). There is some debate concerning whether consideration of a tropospheric polar vortex adds significant new insights to the traditional descriptions in terms of ridges and troughs, or in terms of waves propagating along the upper tropospheric jet stream (Waugh et al 2017, Manney et al 2022.…”
Section: Earth's Tropospheric Polar Vorticesmentioning
confidence: 99%
See 2 more Smart Citations
“…The term "tropospheric polar vortex" has a much more limited use in the scientific literature than that of "stratospheric polar vortex." However, following the extreme cold air outbreak over the United States in 2014, polar vortices have received a lot of attention in the mainstream media and popular science websites, which has resulted in increased usage in the scientific literature (see Manney et al 2022). There is some debate concerning whether consideration of a tropospheric polar vortex adds significant new insights to the traditional descriptions in terms of ridges and troughs, or in terms of waves propagating along the upper tropospheric jet stream (Waugh et al 2017, Manney et al 2022.…”
Section: Earth's Tropospheric Polar Vorticesmentioning
confidence: 99%
“…However, following the extreme cold air outbreak over the United States in 2014, polar vortices have received a lot of attention in the mainstream media and popular science websites, which has resulted in increased usage in the scientific literature (see Manney et al 2022). There is some debate concerning whether consideration of a tropospheric polar vortex adds significant new insights to the traditional descriptions in terms of ridges and troughs, or in terms of waves propagating along the upper tropospheric jet stream (Waugh et al 2017, Manney et al 2022. Manney et al (2022) suggested that salient features of the tropospheric circulation can most clearly be described in relation to the tropospheric jet streams, without invoking the term "tropospheric polar vortex."…”
Section: Earth's Tropospheric Polar Vorticesmentioning
confidence: 99%
See 1 more Smart Citation
“…A commentary in this special collection (Manney, Butler, et al., 2022) discusses the uses and misuses of the term “polar vortex” in popular media as well as scientific literature. They argue that while this well‐established term accurately describes a well‐defined major feature that dominates the circulation in the polar winter stratosphere, attempting to use this term to describe the tropospheric circulation is misguided as that circulation is best characterized in terms of regional undulations of jet streams and the conventional language of ridges and troughs.…”
Section: Introductionmentioning
confidence: 99%
“…However, no dates from the winter of 2013/2014 are included in the compendium of major SSW events (Butler et al, 2017;ESRL, 2020). These observations led to confusion in using the term polar vortex among scientists and in the media (ABC News, 2014;AIR, 2014;Manney et al, 2022;Waugh et al, 2017).…”
mentioning
confidence: 99%